Tax avoidance determinants and earnings management in Indonesian consumer companies - Safira , Dina Maylinda; Setiyawati, Hari (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2024)
This research investigates tax avoidance practices and earnings management among Indonesian consumer companies. The study examines the influence of thin capitalization, transfer pricing, and company life cycle on tax avoidance behaviors and their subsequent impact on earnings management. A total of 115 observations were obtained from 23 companies that were listed on the Indonesia Stock Exchange over a 5-year period (2018-2022) using purposive sampling. Panel data regression analysis revealed that thin capitalization negatively affects tax avoidance, while transfer pricing and company life cycle show no significant impact. Transfer pricing and company life cycle positively influence earnings management, while tax avoidance demonstrates a significant negative effect. These findings contribute to understanding corporate tax behavior and financial reporting quality in Indonesia's consumer sector and provide insights for regulators and investors.